Implementación de un modelo operacional en el estuario del Guadalquivir (SO, España). - Muñoz-López, Pablo; Sammartino, Simone; Nadal Arizo, Irene; García-Lafuente, Jesús; Bejarano Moreno, Antonio (My University, 2023)
The Guadalquivir estuary (SW, Spain) is a critical point of conflicts of interest due to its complexity and interactions between natural factors and human activities. The estuary hosts the only inland port in Spain, the Port of Seville, which handles an average annual traffic of 4-5 million tons and serves both commercial and tourist ships. The main economic enterprises along its margins are based on rice and vegetables cultivation. All these activities imply major alterations of the river environment, such as the dredging of the navigation channel, or the conversion of the original salt marshes into farming fields. Moreover, the UNESCO Biosphere Reserve DOÑANA covers a significant portion of the estuary mouth, with all the ecological entailments that it implies. In order to maintain and optimize its maritime activities, the Seville Port Authority has to cope with all the stakeholders involved in a challenging management of the estuary way. To this aim, an operational numerical model of the estuary dynamics stands out as a key tool for monitoring and predicting physical changes, providing crucial information for decision-making, planning actions, and maritime traffic optimization. The model is forced by forecasts provided by NIVMAR storm surge regional model, the HARMONIE meteorological model and a series of real-time observations and statistically inferred predictions coming from the Guadalquivir Watershed Management Centre (SAIH). The model runs every 12h, providing a 72-h forecast of water level, 3D velocity and thermohaline properties of the column water. The model results are validated against observations, demonstrating its satisfactory performance.
Keywords: Estuario del Guadalquivir; Análisis numérico; Métodos de simulación; Modelo numérico; Modelo operacional; Guadalquivir; DELFT3D